Critical Thinking in Computer Students Considering Virtual and Traditional Forms of Education - Leili Mosalanejad; Saeed Sobhanian (Kerman University of Medical Sciences, 2009)
Background & Objective : Developments in science and technology together with rapid obsolescence in findings and previous information necessitates a type of education in which students are continuously engaged in learning and problem solving and enjoy interfacing changes This study was aimed to assess critical thinking in students of virtual and traditional education Methods : In this crosssectional study two groups including 40 senior computer students from Shiraz University (virtual education) and 40 ones from Islamic Azad University (traditional education) participated Data was collected using Watson Glaser Critical Thinking Test including 80 questions in five subscales including inference recognition of assumptions deduction interpretation and evaluation of arguments Results : The mean score ( ± SD) of critical thinking which was 3677( ± 359) in virtual education happened to be higher than traditional educations mean score which was 3515( ± 694) while there was no significant difference In all five subscales of critical thinking the mean score of interpretation skill was significantly higher in virtual education (79) compared to 695 for traditional education (p=00001) Conclusion : Considering improvements of critical thinking in virtual education and according to its multiple advantages like adding to ones self confidence self esteem and independent learning it is suggested to use this type of education alongside the traditional method or as a replacement for teaching theoretical lessons in university courses